Receptor-like Kinases in Plants From Development to Defense - Tax, Frans.; Tax, Frans.; Kemmerling, Birgit.; Kemmerling, Birgit. (Signaling and Communication in Plants,, 2012)
Sequencing projects have revealed the presence of at least several hundred receptor kinases in a typical plant genome.  Receptor kinases are therefore the largest family of primary signal transducers in plants, and their abundance suggests an immense signaling network that we have only just begun to uncover.  Recent research findings indicate that individual receptor kinases fulfill important roles in growth and development, in the recognition of pathogens and symbionts or, in a few examples, in both growth and defense. This volume will focus on the roles of receptor kinases, their signaling pathways, and the ways in which these important signaling proteins are regulated. .